Compassion-Based Education in the Hadith: A Study of the Perspective of Ta'dib Syed Muhammad Naquib al-Attas and Its Relevance to the Love-Based Curriculum - Ainul Azhari (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study examines the concept of compassion-based education in the Prophetic traditions (hadith), its interpretation through Syed Muhammad Naquib al-Attas’ theory of ta’dib, and its relevance to the Love-Based Curriculum (Kurikulum Berbasis Cinta). The research is motivated by contemporary educational challenges, including bullying, violence, intolerance, and declining social empathy, which indicate the need for a more humane educational paradigm. This study employs a library research design using a thematic hadith (maudhu’i) approach combined with conceptual and philosophical analyses. Primary sources include hadiths on rahmah (compassion) found in Sahih al-Bukhari, Sahih Muslim, Sunan Abi Dawud, and Jami’ al-Tirmidhi, as well as the educational works of Syed Muhammad Naquib al-Attas and literature on the Love-Based Curriculum. Data were analyzed through hadith inventory, takhrij, textual interpretation, analysis of the ta’dib concept, and examination of its relevance to the curriculum. The findings reveal three major typologies of compassion-related hadiths: compassion toward children, compassion toward fellow human beings, and gentleness in educational interactions. These hadiths generate five core educational values: empathy, social care, respect for human dignity, pedagogical gentleness, and exemplary conduct. From the perspective of ta’dib, these values function as instruments for cultivating adab and forming the insan adabi (civilized human being). The study further demonstrates that these values strongly correspond to the pillars of the Love-Based Curriculum, namely love for God, fellow human beings, knowledge, and the environment. This research proposes an integrative model of Hadith of Compassion–Ta’dib–Love-Based Curriculum, positioning compassion as the educational foundation, ta’dib as the philosophical framework for character formation, and the Love-Based Curriculum as its practical implementation in contemporary Islamic education.